Paradoxes of Social Support in Virtual Support Communities: A Mixed-Method Inquiry of the Social Dynamics in Health and Wellness Facebook Groups. Issue 1 (February 2022) - Babić Rosario, Ana; Russell, Cristel Antonia; Shanahan, Doreen Ellen
From parenting to health and wellness, the number of virtual support communities (VSCs) keeps growing. The interactive marketing discipline has primarily documented the positive social dynamics of VSCs: communities provide informational and socio-emotional support that helps members achieve their goals. Yet evidence is mounting that VSCs also exhibit judgment and pressure that ultimately hurt community relationships and engagement. We adopted a mixed-methods approach: a qualitative phase, comprised of netnography and interviews, to explore members' experiences of a VSC and its complex social dynamics, followed by a quantitative phase to test the emerging model with cross-sectional survey data collected from members of a large number of health- and wellness-related VSCs. The two studies provide empirical evidence of many paradoxical social dynamics of VSCs and their relational and engagement consequences. We find that positive group perceptions can generate the social empathy that ensures the group's informational value is helpful to members' goals; however, we also find that negative group perceptions create social pressure that can be helpful to relational and engagement outcomes if it increases social empathy but can also be detrimental if it turns into angst. Our findings contribute to research on VSCs, inform interactive marketing practices, and suggest further research opportunities on the social dynamics of VSCs.